2008
DOI: 10.1183/09031936.00169307
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite DNA instability and COPD exacerbations

Abstract: Increased frequency of microsatellite DNA instability (MSI) has been detected in the sputum of chronic obstructive pulmonary disease (COPD) patients. The aim of the present study was to investigate the relationship between MSI in sputum cells and exacerbation frequency, which is an important parameter in the clinical course of the disease.Induced sputum samples and peripheral blood obtained from 36 patients with COPD at stable state were analysed. The control group consisted of 30 nonsmoking healthy subjects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
2
18
0
3
Order By: Relevance
“…We have recently detected microsatellite DNA instability (MSI) and/or loss of heterozygosity (LOH) in sputum cells of COPD and asthmatic patients. [5,7,[18][19][20]. To our knowledge MSI and/or LOH have not yet been detected in BAL samples from COPD patients.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…We have recently detected microsatellite DNA instability (MSI) and/or loss of heterozygosity (LOH) in sputum cells of COPD and asthmatic patients. [5,7,[18][19][20]. To our knowledge MSI and/or LOH have not yet been detected in BAL samples from COPD patients.…”
Section: Introductionmentioning
confidence: 73%
“…antigen, IL4, beta-adrenergic receptor, tumour necrosis factor, serine proteinase inhibitor genes (serpines), protease inhibitor (PI6, and PI9) endothelin, perforin, α1-antitrypsin, apoptosis-antagonising transcription factor [5,[19][20]. This marker targets a locus in chromosomal region 5q near the coding region for interleukin 4 (IL-4), a pro-inflammatory cytokine that is upregulated and associated with mucous cell hyperplasia and mucus hypersecretion in COPD patients [27,28].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggested that somatic mutations could be involved in the pathogenesis of the disease. [31] Mitochondrial DNA damage Mitochondrial DNA (mtDNA) contributes to oxidation resistance, which is an important determinant that affects COPD susceptibility. It was reported that mtDNA is about 30-fold more sensitive to exogenous oxidants than nuclear DNA.…”
Section: Dna Dsbsmentioning
confidence: 99%